The Use of Genetic Variability Analysis of Fusarium oxysporum f. sp. cubense for Breeding Resistance of Banana against Fusarium Wilting Disease - Faria Ruhana (Universitas Gadjah Mada, 2007)
Fusarium wilting on banana crop caused by Fusarium oxysporum f. sp. cubense is one of the important disease in banana plant in Indonesia. This disease can cause plant to wilt and die, therefore bringing loss to the banana farmer and entrepreneur. F. oxysporum f. sp. cubense genetic variability analysis techniques can be done by in vitro or in vivo. One of F.oxysporum f. sp. cubense genetic variability analysis techniques by in vitro is RAPD-PCR. In this research, analysis is continued with pathogen test. Genetic variability analysis by in vivo is needed to determine the level of pathogen and the race. The result of genetic variability techniques by RAPD-PCR done by this writer indicates that there is a big relation/link difference between isolats from different island. Isolat from Mojokerto (East Java) is 100% genetically different compared to the one from West Sumatera. Later, result of pathogen test shows that Pisang Ambon Kuning is the most resilient compared to Pisang Raja and William Cavendish. Based on the level of pathogen, there are two race grouping, which are race 1 that attacks Pisang Ambon Kuning and race 4 that attacks Pisang Raja and William Cavendish. Scott-Knott analysis on 26 isolats results in no real difference between isolats tested.